Human rights in the global information society - Jørgensen, Rikke Frank (Information revolution & global politics., 2006)
International organizations, governments, academia, industry, and the media have all begun to grapple with the information society as a global policy issue. The first United Nations World Summit on the Information Society (WSIS), held in December 2003, recognized the connections between information technology and human rights with a Declaration of Principles--in effect, the first "constitution" for cyberspace--that called for the development of the information society to conform to recognized standards of human rights. Critical issues in the policy debates around WSIS have been the so-called digital divide, which reflects a knowledge divide, a social divide, and an economic divide; and the need for a nondiscriminatory information society to provide universal access to information technology in local languages throughout the developing world. Other crucial issues include the regulatory frameworks for information access and ownership and such basic freedoms as the right to privacy. The contributors to this timely volume examine the links between information technology and human rights from a range of disciplinary perspectives. Scholars, human rights activists, and practitioners discuss such topics as freedom of expression, access to information, privacy, discrimination, gender equality, intellectual property, political participation, and freedom of assembly in the context of the revolution in information and communication technology, exploring the ways in which the information society can either advance human rights around the world or threaten them. An afterword reports on the November 2005 WSIS, held in Tunis, and its reaffirmation of the fundamental role of human rights in the global information society. Contributors:David Banisar, William Drake, Ran Greenstein, Anriette Esterhuysen, Robin Gross, Gus Hosein, Heike Jensen, Rikke Frank Jorgensen, Hans Klein, Charley Lewis, Meryem Marzouki, Birgitte Kofod Olsen, Kay Raseroka, Adama Samassǩou, Mandana Zarrehparvar.